2022
DOI: 10.1371/journal.pone.0267023
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and prognosis of acute kidney injury in hospitalized patients with acute cholangitis

Abstract: Background The association between acute cholangitis (AC) and acute kidney injury (AKI) remains unclear. We investigated the incidence, and clinical course of AKI in patients with AC, and the long-term prognosis. Methods We performed a single-center retrospective study of patients hospitalized with AC in a tertiary care center from January 2011 to December 2017. The risk factors for AKI were evaluated, and AKI severity was analyzed using the Systemic Inflammatory Response System (SIRS), quick sequential orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Therefore, the attending physician may have preferred PTBD because it is considered to be less invasive and does not require moderate sedation/general anesthesia [5]. Consistently with previous studies [20,21], elevated creatinine levels were associated with acute cholangitis mortality in our study. Elsewhere, a French study reported that the SOFA score (OR 1.14, 95% CI 1.05-1.24) was associated with the in-hospital mortality of patients admitted to the ICU with acute cholangitis [22].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the attending physician may have preferred PTBD because it is considered to be less invasive and does not require moderate sedation/general anesthesia [5]. Consistently with previous studies [20,21], elevated creatinine levels were associated with acute cholangitis mortality in our study. Elsewhere, a French study reported that the SOFA score (OR 1.14, 95% CI 1.05-1.24) was associated with the in-hospital mortality of patients admitted to the ICU with acute cholangitis [22].…”
Section: Discussionsupporting
confidence: 89%
“…AKI (HR = 1.853, 95% CI = 1.115–3.079) was an independent predictor of all-cause acute cholangitis mortality. 38 Our results confirmed that chronic kidney disease was also identified as possible independent risk factors for recurrence of acute cholangitis. The effect of acute kidney injury and chronic kidney injury on recurrence of acute cholangitis remains to be further explored.…”
Section: Discussionsupporting
confidence: 84%
“…Most of these patients are unwell and dehydrated on admission due to sepsis, which is a risk factor for developing AKI. The association of AKI with high mortality in patients with acute cholangitis has been recently published as an independent predictor for mortality, highlighting the importance of early recognition and treatment (10). However, there is a paucity of data demonstrating this in patients with acute cholecystitis undergoing PC.…”
Section: Discussionmentioning
confidence: 99%